El efecto ondulatorio de las fuentes en un Estado Constitucional de Derecho - Hakansson Nieto, Carlos (2015)
The sources of law, as we know them, have been designed under the concept of law of the romangerman system tradition. But, what is the role andposition of the sources of law in a Constitutional State   of   Law,   taking   into   account   that   theConstitution has, according to the author, its originon the Common Law System? Do the sources oflaw lose their utility or have to be rethought?In this article, the author introduces a succession of sources that come from the Constitution, with the aid of jurisprudence, as an undulatory effect thatirradiates all the constitutional legal order.